Capital Structure and Leverage in Private Equity Buyouts. Issue 3 (22nd November 2021) - Brown, Greg; Harris, Robert; Munday, Shawn
Abstract : Private equity capital structures have evolved over time as financial markets and PE firms have created new ways to attract debt capital. In addition to borrowing by individual portfolio companies, debt is being backed by the fund or the general partner, producing different incentive and risk‐sharing features. The use of leverage has been a central feature of the PE model by, first of all, making possible a concentrated ownership position. Studies show that this model has created value for investors and can improve management of the underlying assets. What's more, PE's demonstrated effectiveness in reducing the potential costs of financial distress created by leverage is viewed as evidence of its "comparative advantage" in managing high leverage—one that effectively enables PE‐backed firms to take on higher levels of debt than comparable public companies. Nevertheless, PE structures have the potential to introduce agency conflicts of interests and incentives between GPs and LPs that may be managed with only partial success through contractual arrangements. The outcomes of capital structure decisions in PE vary considerably across the cycle, with rises and falls in leverage and concomitant changes in investment and returns. A number of studies offer explanations of the highly cyclical nature of private equity activity, suggesting that institutional features combined with macroeconomic cycles are to some degree "hardwired" into the industry. In providing evidence of continuing PE outperformance of public companies, the authors also show that the relationship between debt and performance depends on how leverage is measured. When debt is measured as a percentage of deal value, higher leverage is associated with higher average returns, reflecting the positive risk‐return trade‐off that basic finance theory would predict. But when leverage is measured as a multiple of EBITDA—as industry practitioners tend to do—the relationship with performance is weak and negative, suggesting that companies with high debt‐to‐value ratios are more likely to be mature "value" firms, whereas companies with high leverage ratios tilt towards "growth."